2021
DOI: 10.3892/ol.2021.12466
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of hub genes in bladder cancer by bioinformatics analysis and KIF11 is a potential prognostic biomarker

Abstract: Bladder cancer (BC) is the ninth most common lethal malignancy worldwide. Great efforts have been devoted to clarify the pathogenesis of BC, but the underlying molecular mechanisms remain unclear. To screen for the genes associated with the progression and carcinogenesis of BC, three datasets were obtained from the Gene Expression Omnibus. A total of 37 tumor and 16 non-cancerous samples were analyzed to identify differentially expressed genes (DEGs). Subsequently, 141 genes were identified, including 55 upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
3
4
0
Order By: Relevance
“…This outcome could be influenced by different data processing or updated survival information. Thus, we further used, OncoLnc (http://www.oncolnc.org/) and the Kaplan Meier plotter method (27,28) to further update and analyze these data, the final results were consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 75%
“…This outcome could be influenced by different data processing or updated survival information. Thus, we further used, OncoLnc (http://www.oncolnc.org/) and the Kaplan Meier plotter method (27,28) to further update and analyze these data, the final results were consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 75%
“…Apart from CENPA-containing chromatin assembly, it is involved in the regulation of DNA binding activity, chromosomal segregation, cell mitosis, and regulation of protein-containing complex assembly. Our analysis confirmed previous bioinformatics studies in which HJURP was suggested to be a key hub gene for BCa [157,209]. R. Cao et al found that HJURP is highly overexpressed in BCa tissues at both mRNA and protein levels and suggested that HJURP might regulate cell proliferation and apoptosis in BCa by acting on the PPARγ-SIRT1 negative feedback loop [210].…”
Section: Discussionsupporting
confidence: 91%
“…Hence, CDT1 is highly associated with the cell cycle, cell division, DNA replication, and mitosis. In our study, CDT1 was overexpressed in bladder tissue and urine of BCa patients, which was also confirmed by X. C. Mo et al [157], whereas it was significantly under-expressed in the blood plasma of BCa patients. CDT1 has been considered to contribute to cell proliferation and genome instability [158] and to be often misregulated in cancer [159].…”
Section: Discussionsupporting
confidence: 90%
“…KIF11, also known as kinesin spindle protein, is important during mitogenesis and cell proliferation [ 40 ]. Furthermore, KIF11 is upregulated in various human cancers, including bladder cancer, renal clear cell carcinomas, prostate carcinomas, meningiomas, breast cancer, and gastric ccancer [ 41 , 42 ]. Because high levels of the KIF11 expression indicate robust cell proliferation, anti-KIF11 therapy is emerging as a promising cancer therapy approach.…”
Section: Discussionmentioning
confidence: 99%